Quantitative assessment of p16 expression in FNA specimens from head and neck squamous cell carcinoma and correlation with HPV status. Issue 5 (28th December 2020) - Abi‐Raad, Rita; Prasad, Manju L.; Gilani, Syed; Garritano, James; Barlow, Deborah; Cai, Guoping; Adeniran, Adebowale J.
Abstract : Background: This study investigated p16 by immunohistochemistry (IHC) on cellblocks (CBs) and human papillomavirus (HPV) by polymerase chain reaction (PCR) in fine‐needle aspiration (FNA) of head and neck squamous cell carcinoma (HNSCC). Methods: Receiver operating characteristic (ROC) curve analysis was used to assess test performance in CBs compared with p16 IHC in 42 surgical specimens from patients with HNSCC and in correlation with HPV by PCR in cytology specimens. The study assessed HPV by PCR in FNA specimens as a substitute for p16 IHC in surgical specimens. Results: Of 42 cases, 38 CBs showed malignant cells as cohesive clusters of viable cells with or without single tumor cells, whereas 4 specimens were composed exclusively of single tumor cells and degenerated cells. All p16‐negative surgical specimens showed an absence of p16 staining in the corresponding CBs (n = 16). In the p16‐positive surgical cases (n = 26), corresponding CBs with tumor clusters (n = 23) showed heterogeneous p16 expression ranging from 40% to 100%; however, scoring single cells was challenging and unreliable because of cellular degradation. ROC curve inspection showed the optimal threshold to be at least 40% p16 staining in tumor clusters with 100% sensitivity and specificity. In cases with inadequate CBs, HPV by PCR on needle rinse showed 88% sensitivity and 100% specificity for p16 expression in surgical specimens. Conclusions: A cutoff of at least 40% p16 expression in tumor clusters may be appropriate for p16 positivity in cytology CB specimens. A positive HPV finding by PCR on needle rinse can be used as a substitute for p16 expression in surgical specimens. Abstract : Cytology fine‐needle aspiration specimens with tumor clusters in cellblock sections are reliable in determining p16 status by immunohistochemistry in head and neck squamous cell carcinoma. A cutoff of at least 40% in tumor clusters correlates with positive human papillomavirus in cytology specimens and p16 immunohistochemistry in surgical specimens.